2000
DOI: 10.1007/s007010050458
|View full text |Cite
|
Sign up to set email alerts
|

Intraneural Growth of a Capillary Haemangioma of the Cauda Equina

Abstract: Solitary intraneural haemangiomas are very rare. A case of intraneural capillary haemangioma involving two nerve roots of the cauda equina is reported. The patient was a 63-year-old woman with a three years history of intermittent lumbalgia and numbness of the ventral surface of the left thigh. Magnetic resonance imaging detected an intradural extramedullary nodular space occupying mass at the level of the conus medullaris. Laminectomy of T12 and complete removal of the tumour were performed. Histopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 17 publications
4
60
0
Order By: Relevance
“…[1][2][3][4]6,15 The most common location of these vascular malformations is the supratentorial cerebral parenchyma. Cauda equina nerve root is a very rare location.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4]6,15 The most common location of these vascular malformations is the supratentorial cerebral parenchyma. Cauda equina nerve root is a very rare location.…”
Section: Discussionmentioning
confidence: 99%
“…Cauda equina nerve root is a very rare location. 4,[9][10][11][12][13][15][16][17][18][19][21][22][23][24][25][26] Pagni et al 15 reviewed all intradural cavernous angioma of the spine described in the literature. They concluded that subdural extramedullary cavernous angiomas are the most rare of the cavernomas with only 10 cases documented between 1903 and 1990.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Involved nerves have included the trigeminal, ulnar, median, digital, posterior tibial, and peroneal nerves [16,18,24,34,41]. Solitary intraneural hemangiomas within the sheaths of a lumbar spinal nerve root [22] and a nerve root of the cauda equina have also been reported [25]. Among the 13 cases reported in the literature [2, 6, 16-18, 20, 23, 24, 29-31, 42], there is no characteristic anatomic distribution; the median nerve is most commonly affected (six cases), followed by the tibial (three cases), ulnar, digital, sciatic, and superficial peroneal nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 13 cases reported in the literature [2, 6, 16-18, 20, 23, 24, 29-31, 42], there is no characteristic anatomic distribution; the median nerve is most commonly affected (six cases), followed by the tibial (three cases), ulnar, digital, sciatic, and superficial peroneal nerves. Solitary intraneural hemangiomas, confined to one or more nerve roots of the cauda equina [22,25] and the inferior trunk of the brachial plexus [3], have also been reported. All but one intraneural hemangioma occurred in children and young adults younger than 40 years; in all but two of the reported cases, the patients were women [3,41].…”
Section: Discussionmentioning
confidence: 99%